Learners' anxiety & self-efficacy in practicing speaking outside the classroom - Suryanto, Dodi; Muthmainnah, Nur (Nur Science Institute, 2024)
Self-efficacy and anxiety were two psychological aspects that were influential in improving the students’ speaking skills. This study aimed to investigate the correlation between learners' anxiety and their self-efficacy when they are forced to practice speaking outside the classroom. It involved 30 members of the speaking community, which was offered by the campus to improve students' English capability outside the classrooms. They were given two questionnaires confirming their self-efficacy and their anxiety. Average students were classified into low categories of their self-efficacy and anxiety. this investigation showed the there was no correlation between these two varibles. As the level of significance of this correlation reached 0.007 > 0.005. Thus, students’ speaking anxiety had not proven to be correlated with students’ self-efficacy when they tried to speak English outside the classrooms. A deeper study is needed to accomplish this study in the form of investigating narratively how students’ cope their anxiety and raise their self-efficacy.